Mitochondrial dysfunction in a mouse model of prodromal Parkinson's disease: A metabolomic analysis. (20th November 2021) - Ikuno, Masashi; Yamakado, Hodaka; Amano, Ikuko; Hatanaka, Yusuke; Uemura, Norihito; Matsuzawa, Shu-ichi; Takahashi, Ryosuke
Highlights: Metabolomic analysis of the plasma from a mouse model of prodromal PD (p-PD). Increased levels of isobutyrylcarnitine imply an abnormality in β-oxidation. Systemic mitochondrial dysfunction may exist and contribute to the pathogenesis. Abstract: For the development of disease-modifying therapies for Parkinson's disease (PD) the identification of biomarkers in the prodromal stage is urgently required. Because PD is considered a systemic disease even in the early stage, we performed a metabolomic analysis of the plasma from a mouse model of prodromal PD (p-PD). Increased levels of isobutyrylcarnitine in p-PD mice imply an abnormality in β-oxidation in mitochondria, and increased levels of pyrimidine nucleoside can be associated with mitochondrial dysfunction. Consistent with these results, the immunoblot analysis showed a defect in mitochondrial complex I assembly in p-PD mice. These results suggest that systemic mitochondrial dysfunction may exist in p-PD mice and contribute to the pathogenesis of PD, potentially being useful as early biomarkers for PD.